Linguistic Elitism: the Advantage of Speaking Irish Rather than the Irish-speaker Advantage - Watson, Iarfhlaith; Nic Ghiolla Phádgraig, Máire (Economic & Social Studies, 2011)
This paper contributes to the discussion of linguistic elitism in this journal (Borooah et al., 2009). Two main questions are addressed. First, most “census Irish speakers” are not in fact Irish speakers and the majority of Irish speakers proper are not a coherent group. Second, the Irish language is part of the cultural capital which can be acquired by people with an “advantage.” The argument is made that people with an advantage are more likely to speak Irish rather than Irish speakers being more likely to have an advantage.
Keywords: Language use; Irish; linguistic elitism